Managing electronic government information in libraries issues and practices - Morrison, Andrea Marie 1957- (American Library Association, 2008)
In two parts, this expert guide from ALA's Government Documents Round Table (GODORT) describes indispensable resources librarians can use to connect patrons to specific information via government sites and electronic documents. In part 1, the contributing authors discuss historical contexts and contemporary issues of electronic government collections. In part 2, they give practical guidance for implementing and improving services. Libraries of all types will find this book a bridge to serving more patrons through electronic government collections.